Oleuropein and hydroxytyrosol as antidiabetics: a review on extraction method, effectiveness and toxicity effect - Harun, Nurhidayati; Ketut Adnyana, I; Damayanti, Sophi; Kurniati, Neng Fisheri (Vojenské zdravotnické listy, 2024)
Introduction: Olive (Olea uropeae) is a traditional plant containing oleuropein and hydroxytyrosol, which are useful and used empirically for treating diabetes mellitus.Objective: To review the potential of oleuropein and hydroxytyrosol as an evidence base for diabetes potential treatment and safety.Methods: This chapter summarizes several studies available on Pubmed and Google Scholar regarding the characteristic method and extraction method as well as the effectiveness and toxicity of oleuropein and hydroxytyrosol in vitro and in vivo.Result: Oleuropein and hydroxytyrosol are effective antihyperglycemics for treating T2D. They can reduce body weight, basal glycemia, and insulin resistance by stopping the liver from making glucose and stopping the body from absorbing glucose. Several studies have shown that both isolates can control glycemic levels equivalent to free fatty acids and are safe to use.Conclusion: Oleuropein and hydroxytyrosol are extracted by several methods and can be used as potential anti-diabetics with obesity risk factors. Evidence shows that both isolates are safe for both acute and chronic use.
Keywords: Diabetes Mellitus, Type 2; Toxicity Tests; Hypoglycemic Agents; Iridoids; oleuropein; hypoglykemika; Plant Extracts; iridoidy; testy toxicity; Humans; Olea; lidé; diabetes mellitus 2. typu; inzulinová rezistence; Insulin Resistance; hydroxytyrosol; rostlinné extrakty